Changes in Tinnitus Experiences During the COVID-19 Pandemic - Beukes, Eldré W.; Baguley, David M.; Jacquemin, Laure; Lourenco, Matheus P. C. G.; Allen, Peter M.; Onozuka, Joy; Stockdale, David; Kaldo, Viktor; Andersson, Gerhard; Manchaiah, Vinaya (Frontiers in Public Health, 2020)
Introduction: The COVID-19 pandemic has disrupted delivery of healthcare, economic activity, and affected social interactions. Identifying and supporting those most affected by the pandemic is required. The purpose of this study was to determine the impact of the pandemic on individuals with tinnitus and to identify mediating factors. Methods: This is a mixed-methods exploratory cross-sectional study, using data collected via an online survey from 3,103 individuals with tinnitus from 48 countries. The greatest representation was from North America (49%) and Europe (47%) and other counties were only marginally represented. Results: Although the study was aimed at those with pre-existing tinnitus, 7 individuals reported that having COVID-19 initiated tinnitus. Having been diagnosed with COVID-19 exacerbated tinnitus in 42% of respondents, made no change in 57%, and improved tinnitus in 1%. Other mediating factors such as the social and emotional consequences of the pandemic made pre-existing tinnitus more bothersome for 32% of the respondents, particularly for females and younger adults, better for 1%, and made no change to tinnitus for 67%. Pre-existing tinnitus was significantly exacerbated for those self-isolating, experiencing loneliness, sleeping poorly, and with reduced levels of exercise. Increased depression, anxiety, irritability, and financial worries further significantly contributed to tinnitus being more bothersome during the pandemic period. Conclusions: These findings have implications for tinnitus management. They highlight the diverse response both internal and external factors have on tinnitus levels. Clinical services should be mindful that tinnitus may be initiated by contracting COVID-19 and pre-existing tinnitus may be exacerbated, although in the majority of respondents there was no change. Additional support should be offered where tinnitus severity has increased due to the health, social, and/or emotional effects of the COVID-19 pandemic. Tinnitus may be more bothersome for those experiencing loneliness, having fewer social interactions, and who are more anxious or worried.